2013
DOI: 10.1073/pnas.1303251110
|View full text |Cite
|
Sign up to set email alerts
|

Genome of Phaeocystis globosa virus PgV-16T highlights the common ancestry of the largest known DNA viruses infecting eukaryotes

Abstract: Large dsDNA viruses are involved in the population control of many globally distributed species of eukaryotic phytoplankton and have a prominent role in bloom termination. The genus Phaeocystis ( Haptophyta , Prymnesiophyceae ) includes several high-biomass-forming phytoplankton species, such as Phaeocystis globosa , the blooms of which occur mostly in the coastal zone of the North Atlantic and the North Sea. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
217
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 176 publications
(226 citation statements)
references
References 35 publications
6
217
2
1
Order By: Relevance
“…Finally the Pithovirus genome is predicted to encode a mere 467 proteins, much less than the 2,500 predicted proteins of Pandoravirus salinus. The Pithovirus particle appears to be out of proportion with its gene content compared with other DNA viruses such as the Phaeocystis globosa virus packing a similar number of genes into an icosahedral capsid 150 nm in diameter (150-fold less in volume) (19).…”
Section: Resultsmentioning
confidence: 99%
“…Finally the Pithovirus genome is predicted to encode a mere 467 proteins, much less than the 2,500 predicted proteins of Pandoravirus salinus. The Pithovirus particle appears to be out of proportion with its gene content compared with other DNA viruses such as the Phaeocystis globosa virus packing a similar number of genes into an icosahedral capsid 150 nm in diameter (150-fold less in volume) (19).…”
Section: Resultsmentioning
confidence: 99%
“…1 and Supplementary Data 2), suggesting that such classification scheme might not prove to be practical. (4) and tombusviruses (48). Whiskers correspond to the R ggplot library geom_boxplot function default paramers (for upper whisker: the highest value that is within 1.5*Inter-Quartile Range of the hinge, and for lower whisker: the smallest value that is within 1.5*Inter-Quartile Range of the hinge).…”
Section: Discussionmentioning
confidence: 99%
“…At any rate, the association of different CHIV contigs with two different types of eukaryotes raises an intriguing possibility that unicellular eukaryotes serve as hosts for at least some CHIVs. Interestingly, we identified a close homologue (AET73220; E ¼ 4e À 29, 35% identity) of CHIV12 RC-Rep (but not the CP) encoded in the genome of a giant double-stranded DNA virus, PgV-12T, infecting Phaeocystis globosa 48 , a photosynthetic unicellular algae. It has been recently demonstrated that satellite viruses and transposons integrate into the genome of the Lentille virus, a relative of mimiviruses 49 .…”
Section: 00mentioning
confidence: 99%
“…Prior to defining these two genera, metagenomic studies had already hinted at the presence of mimivirus relatives in marine environments (6). The successful isolation and characterization of several of these viruses showed that they correspond to smaller icosahedral particles (140 to 180 nm in diameter) packing smaller dsDNA genomes (370 to 475 kb in length) (7)(8)(9). In core gene phylogenies, these viruses clearly cluster with the Mimiviridae, although they appear to constitute a distinct clade ( Fig.…”
mentioning
confidence: 99%